Implementation of Qurma Learning in Developing Speaking Skills in Fourth Grade Students at Islamic Elementary School (MI) Narrative Qur'an Lamongan - Fitratul Uyun; Putri Septiani Eka Irwanti (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
Speaking skill is a very important role in elementary school. Speaking skills are mechanistic, meaning that speaking skills are acquired through a continuous process of practice. The purpose of this research is to describe an implementation of Qur'an learning (Qur'an and meaning) in developing speaking skills in fourth-class students at Elementary school Islamic Narrative Qur'an Lamongan. This research used a qualitative approach with a qualitative descriptive research type. The data collection techniques in this research were interviews, observation, and documentation. This research used data analysis in the form of data reduction, data presentation, and conclusion. The validity of the data was tested using triangulation of sources and techniques. The results of the research indicate the implementation of Qurma learning at Elementary schools Islamic Narrative Qur'an Lamongan includes planning, implementing, and evaluating learning. The growth of speaking skills in students through learning Qurma is marking by choosing words that are easy to understand, placement of appropriate intonation, self-confidence, mastering the topic of the story being told, fluency and accuracy of speech, and courage.